The assessment of aspirin resistance by using light transmission and multiple electrode aggregometry - Ulehlova, J; Slavik, L; Krcova, V; Hutyra, M; Galuszka, J; Indrak, K (International journal of laboratory hematology, 2011)
INTRODUCTION: The issues related to aspirin [acetylsalicylic acid (ASA)] resistance are still under debate. Depending on the method of assessment and studied patients, the prevalence of ASA resistance is rather heterogeneous, ranging from 5% to 45%. The method most commonly used for assessing platelet function is their aggregation. ASA irreversibly inhibits cyclooxygenase-1 (COX-1) by acetylation. METHODS: This study aimed to compare light transmission aggregometry (LTA) and multiple electrode aggregometry (MEA) for the measurement of ASA resistance, using arachidonic acid as an inducer of the reaction. RESULTS: The study comprised 101 patients with stable ischemic heart disease taking a daily dose of 100 mg of ASA. The rates of ASA resistance were 22.22% and 21.21% as detected by LTA and MEA, respectively. The two methods were statistically compared using Spearman's nonparametric correlation analysis, with a positive significant correlation (P=0.01) and medium positive dependence between the methods (r=0.0539). CONCLUSION: If ASA resistance is detected by laboratory tests, replacement of ASA or its combination with other antiplatelet drugs as well as increased dosage may be considered.
Keywords: dospělí; vyšetření funkce trombocytů; inhibitory agregace trombocytů; Humans; lidé středního věku; Middle Aged; Platelet Function Tests; Platelet Aggregation; Sensitivity and Specificity; Aspirin; mužské pohlaví; Adult; léková rezistence; ženské pohlaví; Platelet Aggregation Inhibitors; Drug Resistance; lidé; senzitivita a specificita; Aged; senioři; Male; agregace trombocytů; Female